Virtual Patients: Impact of Computer Simulation on Audiology Learning and Practice. - de Araújo, Deuzimar Pires; Duarte, Josilene Luciene; Araújo, Eliene Silva (American Journal of Audiology, 2023)
Purpose: The purpose of this study was to verify users' satisfaction with the interface of an audiometric simulator and self-perception of the computer simulation impact on practical acting in audiology, allowing the identification of problems and possibilities for improvement. Method: A prospective, observational study was divided into two phases: The first is evaluating the student's satisfaction, using the simulator in the theoretical and practical learning of audiology, and the second one is assessing the selfperception of the simulator's impact on the practical performance of audiology. The sample comprised 35 students from two Speech-Language Pathology and Audiology courses, in Brazil, selected by convenience, who answered the questionnaire after completing the theoretical module, using Google Forms, without any identification. Results: In the first phase of the study, students positively evaluated the use of the simulator as an auxiliary tool for audiology learning, and in the second one, they also positively assessed the impact of training with the simulator in audiological practice. Conclusion: The analyzed audiometric simulator proved to be an interactive system with high acceptability, level of satisfaction, and potential impact on practical performance in audiology. Supplemental Material: https://doi.org/10.23641/asha.23876325